PENGARUH PENGELOLAAN KELAS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS IV MIS MANARUL HUDA KOTA TASIKMALAYA - Nina (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Learning outcomes are the end of the completion of the learning process in the world of education. To get good learning outcomes, teachers must play an important role in managing the class during the learning process. The learning process at MIS Manarul Huda, Tasikmalaya City, there are still teachers who have not been able to arrange student seats properly, there are still some facilities and infrastructure supporting the learning process that are not adequate. This study aims to determine whether there is an effect of classroom management on student learning outcomes in the Akhlak class IV subject of MIS Manarul Huda, Tasikmalaya City. This research was carried out in May 2022. The sample in this study was 40 students of class IV MIS Manarul Huda in the 2021/2022 academic year. The research method used in this study is a quantitative method with sampling that is saturated sampling. Class management data was taken from a questionnaire with a total of 15 question items, while learning outcomes data were taken from the results of the pre-test and post-test as many as 18 questions, in the kontrol class 20 people and the experimental class 20 people. To analyze the data, the researcher used SPSS software version 20. Based on the calculation of the Faired Samples t-Test, the significance value (2-tailed) 0.000 < 0.05 indicates a significant difference between the initial variable (Pre Test) and the final variable (Post Test). This shows that there is a significant effect on the difference in the treatment given to each variable